Surveying populations of breeding grebes in prairie parkland Canada: Estimation problems and conservation applications - Daniel D. Routhier; Kevin W. Dufour; Mark T. Bidwell; Robert G. Clark (Wildlife Society Bulletin, 2014)
ABSTRACT Annual ground surveys of mid‐continent waterfowl may provide a monitoring framework for other wetland‐associated species. We used a repeated‐counts method to estimate detection probabilities (ρˆ) of adult horned (Podiceps auritus) and pied‐billed (Podylimbus podiceps) grebes on the Waterfowl Breeding Population and Habitat Survey (WBPHS) ground component conducted annually each May in the prairie and parkland ecoregions of Canada. Detection probabilities (ρˆ ± SE) were higher, more precise, and more consistent through time for horned grebes (0.52 ± 0.06 and 0.44 ± 0.05 in 2010 and 2011, respectively) than for pied‐billed grebes (0.25 ± 0.08 and 0.11 ± 0.05 in 2010 and 2011, respectively). Our results suggest that the ground component of the WBPHS could be used to monitor horned grebes in these ecoregions. Although an active call‐broadcast component would be valuable for obtaining unbiased abundance estimates for horned grebes, such a component would be critical for monitoring pied‐billed grebes. © 2013 The Wildlife Society.